Human capital, informality and labour market outcomes in sub-Saharan Africa - Kerr, A (2011)
In this thesis I explore three topics in labour economics, using micro data from South Africa and Tanzania. South Africa suffers from extremely high income inequality, in part as a result of comprehensive Apartheid-era racial discrimination. The first topic explores possible explanations for the extremely large earnings differences across different types of employment for black South Africans, using the KwaZulu-Natal Income Dynamics Study data. I analyse the relative importance of individual ability and institutions, including public sector wage setting and trade unions, in determining earnings. My results suggest that human capital explains much of the earnings differentials within the private sector, including union premiums, but cannot explain the large premiums for public sector workers. Self-employment is very common in urban Tanzania but, unlike South Africa, survey data show that there are large overlaps in the distribution of earnings in private wage employment and self-employment. This suggests that self-employment represents a viable alternative to wage employment in small, low productivity firms for the majority of urban Tanzanians. In chapter three I build an equilibrium search model of the urban Tanzanian labour market to explain the choice of wage and self-employment and the variation in earnings across and within these sectors. In the final topic I explore the effect of education on earnings in Tanzania. Estimating the returns to education has stimulated much recent work in applied econometrics as researchers advance their understanding of the effect of individual heterogeneity on the possibility of estimating the returns to education. In my attempt to purge estimates of the return to education of the influence of individual heterogeneity, I use an education reform in Tanzania as a natural experiment that provides exogenous variation in education. When using Ordinary Least Squares (OLS) I find high and strongly convex, increasing returns to education. My best attempt at separating out the effect of individual heterogeneity suggests that returns are still high but that they may actually be concave.